HOME-MADE REMARKS IN ELEMENTARY SCHOOLS - N. A. Abdukarimov; Toshpo‘latova Maftuna Ikrom qizi (Zeta Repository, 2023)
This article focuses on the topics of the beginner class with an organized childhood. Using a number of methods and methods in the course of the lesson, students will be given an understanding of organized sentences.